The rivers of Zadaa : [compact disc, unabridged] - MacHale, D. J. (MacHale, D. J. Pendragon, 2005)
Taking advantage of a severe drought and the long-standing distrust between two tribes, the demonic Saint Dane attempts to take over Loor's home planet of Zadaa, opposed once again by the teenaged Pendragon and other Travelers.